Twin LIGO/Virgo Detections of a Viable Gravitationally-Lensed Black Hole Merger - Broadhurst, Tom; Smoot, George F.; Diego, Jose M. (NURIS; Energetic Cosmos Laboratory, 2019)
We identify a binary black hole (BBH) merger that appears to be multiply lensed by an intervening galaxy. The LIGO/Virgo events GW170809 and GW170814 have indistinguishable waveforms separated by 5 days, and overlap on the sky within the 90\% credible region. Their strain amplitudes are also similar, implying a modest relative magnification ratio, as expected for a pair of lensed gravitational waves. The phase of the two events is also consistent with being the same, adding more evidence in support of both events originating from the same BBH merger. The difference in the published inferred distances of each event can then be interpreted as following from their different magnifications.
Keywords: The 2nd international conference of the Energetic Cosmos Laboratory (ECL); ECL19; Energetic Cosmos Laboratory (ECL)